A Case of Medication-Resistant Acanthamoeba Keratitis Treated by Corneal Crosslinking in Turkey - Goktug Demirci; Akif Ozdamar (Case Reports in Ophthalmological Medicine)
Purpose. To report a case of medication-resistant acanthamoeba keratitis (AK) treated successfully by corneal crosslinking (CXL). Methods. A 26-year-old male with medication-resistant AK underwent a standard CXL procedure with local anesthesia, followed by central corneal epithelial debridement, application of riboflavin 0.1%, and UV-A irradiation. Results. The patient experienced a dramatic symptomatic improvement within 24 hours. At two months, keratitis was healed with a semitransparent paracentral scar that did not affect visual acuity. Conclusions. Our experience, considered in the context of recent studies, suggests that CXL may be an option for selected patients with medication-resistant AK and corneal melting. CXL allows patients to avoid emergency keratoplasty and experience rapid symptomatic relief.